2022
DOI: 10.1093/jas/skac066
|View full text |Cite
|
Sign up to set email alerts
|

Influence of infection with Brachyspira hyodysenteriae on clinical expression, growth performance, and digestibility in growing pigs fed diets varying in type and level of fiber

Abstract: Research on effects of different fiber types and levels on infection with Brachyspira hyodysenteriae on growth performance and nutrients digestibility in pigs is scarce. The objective of the current study was to investigate the effects of infection with B. hyodysenteriae when feeding diets varying in soluble and insoluble dietary fiber (DF) on the expression of swine dysentery, growth performance and digestibility of organic matter (OM) nutrients. A total of 96 growing pigs (26.9 ± 2.5kg) were used for the exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 34 publications
1
6
0
Order By: Relevance
“…Examples of previous published research help to highlight this point and how challenging Brachyspira inoculation can be. For instance, intragastric inoculation of 40 mL of a strongly hemolytic strain of B. hyodysenteriae (strain B204) broth containing 1 × 10 8 colony forming units (CFU)/mL for 3 days (1.2 × 10 10 CFU total dose) resulted in 55.5% (5/9) SD incidence (Trial 2 of [ 20 ]), whereas intragastric inoculation of 50 mL (1 × 10 9 CFU/mL) of a Danish field isolate of B. hyodysenteriae broth following a similar methodology (1.5 × 10 11 CFU total dose) resulted in only 20.8% (10/48) incidence of SD by another laboratory [ 21 ]. This variability in incidence highlights the need to establish minimum infective doses for the Brachyspira species/strains and experimental conditions specific to each laboratory, and the importance of full disclosing all methodological details in studies to help decipher differences among B. hyodysenteriae strains, environmental factors, and host related factors like genetics and microbiota.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Examples of previous published research help to highlight this point and how challenging Brachyspira inoculation can be. For instance, intragastric inoculation of 40 mL of a strongly hemolytic strain of B. hyodysenteriae (strain B204) broth containing 1 × 10 8 colony forming units (CFU)/mL for 3 days (1.2 × 10 10 CFU total dose) resulted in 55.5% (5/9) SD incidence (Trial 2 of [ 20 ]), whereas intragastric inoculation of 50 mL (1 × 10 9 CFU/mL) of a Danish field isolate of B. hyodysenteriae broth following a similar methodology (1.5 × 10 11 CFU total dose) resulted in only 20.8% (10/48) incidence of SD by another laboratory [ 21 ]. This variability in incidence highlights the need to establish minimum infective doses for the Brachyspira species/strains and experimental conditions specific to each laboratory, and the importance of full disclosing all methodological details in studies to help decipher differences among B. hyodysenteriae strains, environmental factors, and host related factors like genetics and microbiota.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies evaluating different levels of soluble or insoluble dietary fiber have also showed variable results. On one hand, fiber concentration (high vs. low) and type (soluble vs. insoluble) did not effect fecal score in a Danish study, however, this result should be taken with caution due to the low incidence of MMHD across all groups [ 21 ]. On the other hand, several USA studies indicate high concentration of insoluble fiber in the diet promotes expression of SD.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the growing phase, the ADG was decreased in pigs fed the LP diet based on the protein recommendation of the NRC (2012), except almost complete compensatory growth found in finishing pigs. Several factors, including feed restriction, early age growth retardation, and intestinal diseases, can potentially influence compensatory growth [ 30 , 31 , 32 ]. Rao, et al [ 33 ] reported that lysine-restricted feeding in the early phase of finishing pigs decreases growth performance, but recovery was found, showing the magnitude of compensatory growth in the late phase.…”
Section: Discussionmentioning
confidence: 99%
“…In general, a higher percentage of fermentable fiber may be beneficial to pigs for those diets that are based on less highly digestible ingredients (barley, triticale) (Hansen et al, 2010;Hansen et al, 2011), and pigs fed a poorly fermentable fiber diet with high insoluble fibers such as the biofuel coproducts like distillers dried grain with soluble (DDGS) present with a quicker onset of SD and higher disease incidence when challenged with strongly b-hemolytic Brachyspira species (Wilberts et al, 2014a). Conversely, a recent study suggested that expression of SD was likely not strongly associated with fiber type (Lee et al, 2022). The discrepancy in findings among these studies is likely due to the differences in experimental designs and the specific source of dietary fiber.…”
Section: Introductionmentioning
confidence: 89%